PHYTOTHERAPY IN SEASONAL PREVENTION OF ACUTE RESPIRATORY DISEASES AMONG SCHOOL-AGED CHILDREN - T.I. Garashchenko; L.I. Il'enko; M.V. Garashchenko (Вопросы современной педиатрии)
The article provides the research findings of the application efficiency of the complex plant based preparation Sinupret (Bionorica AG, Germany) for prevention of the acute respiratory diseases among sickly children. The authors showed that the application of the plant based preparation decreased the sick rate caused by the acute respiratory diseases and influenza, alleviated the run of the acute respiratory diseases, had some really good tolerance and might be recommended for the wide use, for the prevention of the acute respiratory diseases in organized children groups.Key words: acute respiratory diseases, prevention, phytotherapy, children, homeopathic remedies, vaccines.